2022
DOI: 10.18585/inabj.v14i3.1921
|View full text |Cite
|
Sign up to set email alerts
|

Purple Sweet Potato Yogurt Affects Lipid Metabolism and Reduces Systemic Inflammation and Oxidative Stress in High Fat Diet Mice

Abstract: BACKGROUND: Purple  sweet  potato  yogurt (PSPY) is a funtional food which is rich in anthocyanin and probiotics. However, the currently available data on its potentially protective effect on anthropometry, lipid metabolism, oxidative stress, and pro-inflammatory markers is very minimal, especially in mice. This study was performed to investigate those effects on balb/c mice models (Mus musculus) given a high-fat diet (HFD).METHOD: Balb/c mice were treated with or without standard diet, HFD, ethanol extract, y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…Sugata et al reported the inhibitory effects of anthocyanin from purple-fleshed potatoes in lipopolysaccharide-induced inflammation of RAW-264.7 cells by reducing nuclear factor kappa B (NF-Kb), tumor necrosis factor alpha (TNF-α) and IL-6 following a dose-dependent manner [25]. Correlates with recent results, the supplementation of local purple sweet potatoes reduces the level of IL-6 as well as TNF-α in highfat diet mice [26].…”
Section: Resultsmentioning
confidence: 58%
“…Sugata et al reported the inhibitory effects of anthocyanin from purple-fleshed potatoes in lipopolysaccharide-induced inflammation of RAW-264.7 cells by reducing nuclear factor kappa B (NF-Kb), tumor necrosis factor alpha (TNF-α) and IL-6 following a dose-dependent manner [25]. Correlates with recent results, the supplementation of local purple sweet potatoes reduces the level of IL-6 as well as TNF-α in highfat diet mice [26].…”
Section: Resultsmentioning
confidence: 58%
“…(37) Oxidative stress is caused by the peroxidation of fat cell membranes can observed by examining the level of MDA. (8,38) LN is associated with oxidative stress. ( 12) Expanded peroxidation of cell membrane lipid in LN can cause the arrangement of lipid-derived reactive aldehydes (LDRA) including MDA.…”
Section: Discussionmentioning
confidence: 99%